Analisis Pengaruh Upah dan Tenaga Kerja terhadap Pengangguran di Indonesia dalam Prespektif Ekonomi Islam - Latifah, Tatik; Syarif, Ahmad Hazas; Taufiqurrahman, Taufiqurrahman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the effect of minimum wages and the number of workers on unemployment in Indonesia in the perspective of Islamic economics for the period 2009-2023. This research takes place in Indonesia The research period is 15 years, namely 2018-2023, all data used is obtained from the official BPS website, This study employs a quantitative methodology. Explanatory research is the methodology employed in this study. The authors of this study employed Eviews 10 technologies to make data processing easier. A variation of VAR is the Vector Error Correction Model, or VECM. With the exception of stationarity issues, the same presumptions as VAR must be met. The data used in this analysis, which focuses on Indonesia from 2009 to 2023, was taken from the official BPS website. The study's goal was to ascertain how different variables affected the dependent variable, unemployment (Y), specifically the impact of independent variables, minimum wage (X1) and total labor (X2). The findings demonstrated that the minimum wage variable had a favorable impact on unemployment over the long run (coefficient value: 4.04E07), and over the short term (coefficient value: 3.57E-06). We can conclude that the minimum wage has a favorable impact on the unemployment rate both in the short and long run. Additionally, the number of employees has a long-term positive impact on unemployment (coefficient value: 0.486303), whilst the number of employees has a short-term negative impact (coefficient value: -0.021979) on unemployment in Indonesia. Therefore, it can be said that having more employees offers both short- and long-term benefits.